Environmental Damage and UK Offshore Operations: Uncertain Liabilities in Deep Waters - Simon Baughen (Journal of Environmental Law, 2016)
This article reviews the EU’s response to Deepwater Horizon, culminating in the Offshore Safety Directive 2013 which came into effect in the UK on 19 July 2015, and analyses the current civil liability regime in the UK for dealing with a catastrophic spill in UK waters, the effectiveness of the Offshore Pollution Liability Agreement (“OPOL”), the voluntary agreement to which all UK offshore operators belong, as well as assessing the current regime for the provision of financial security to cover both public law and civil liabilities arising out of offshore operations.